Pemanfaatan Media Video Animasi dan Permainan Tradisional dalam Bimbingan Belajar Siswa SD Selama Masa Pandemi Covid-19 - Maria Silvia Aso; Helena Susanti Anur; Adrianus Nasar (Prima Abdika : Jurnal Pengabdian Masyarakat, 2021)
The purpose of tutoring for the students of SDK Kekandere 2 is to help students understand the material well in the midst of the ongoing Covid-19 pandemic situation. The learning media used during tutoring are animated videos and traditional games as learning methods. The purpose of using animated videos is to make students more enthusiastic about participating in learning and also to increase students' understanding of the material they are learning. Traditional games are used so that students do not get bored easily or students can learn while playing. Besides that, it also helps students to find their own concepts because previously students only got material information from the teacher. And in between learning activities, reading exercises were carried out for students who were not yet fluent in reading. The results of the tutoring carried out can improve students' understanding, students are very enthusiastic about participating in the learning process and students are able to learn to find their own concepts even though they are not perfect. Meanwhile, to read only needs regular practice from students.